Ischemic Hepatitis and Septic Shock Secondary to Murine Typhus Infection in Pregnancy - Berry, Marissa; Wang, Amanda M.; Lahham, Rana F.; Zhang, Xue; Pacheco, Luis D. (American Journal of Perinatology Reports, 2024)
Infection with murine typhus may be associated with significant morbidity. With nonspecific symptoms and laboratory abnormalities, diagnosis may be challenging. In this case, a pregnant patient presented with complaints of fevers and myalgias. Her laboratory results included severe transaminitis as well as thrombocytopenia and hyponatremia. She ultimately required vasopressor support and intensive care unit admission despite fluid resuscitation and broad-spectrum antibiotics. Empiric doxycycline was initiated due to suspicion for murine typhus, which laboratory testing later confirmed. Her clinical status improved with these interventions. This was a severe case of murine typhus resulting in septic shock and ischemic hepatitis. It is important to know the typical findings of murine typhus and consider it in a differential diagnosis, especially when practicing in endemic areas.
Keywords: murine typhus; ischemic hepatitis; septic shock